Bimbingan Teknis Pengajuan Dana Bergilir LPMUKP dan Pembuatan Proposal di SMART Fisheries Village (SFV) Pengambengan, Kabupaten Jembrana, Bali - Aras, Annisa Khairani; Nisa, Andina Chairun; Utami, Diah Ayu Satyari; Kiswanto, Arie; Insani, Liga; Kusmiatun, Anik; Jatayu, Diklawati (Jurnal Pengabdian UNDIKMA, 2024)
The aim of this community service activity is to increase the understanding and skills of the SFV Pengambengan assisted group regarding applications for LPMUKP revolving funds and making whiteleg shrimp cultivation business proposals. This method of implementing community service uses technical guidance with 10 participants representing Pokdakan Mina Jaya and Pokdakan Putra Mina Jaya. Evaluation of this activity took the form of a pre-test and post-test and was analyzed using the t-test with a confidence level of 95% (Î± = 0.05). The results of this community service activity show that the SFV Pengambengan assisted group has increased their understanding regarding applications for LPMUKP revolving funds for aquaculture businesses as well as increased skills in making whiteleg shrimp cultivation business proposals which are used as one of the requirements for applications for LPMUKP revolving funds.